CAM Models: Lessons and Implications for CAM Evolution - Burgos, Asdrubal; Miranda, Enoc; Vilaprinyo, Ester; Meza-Canales, Iván David; Alves, Rui (Frontiers in Plant Science, 2022)
On the onset of climate change, expanding the use of water efficient crops and engineering higher water use efficiency into crops constitute a plausible solution for the problems of agriculture in hotter and drier environments. The evolution of Crassulacean acid metabolism (CAM) by plants was one of the most successful strategies in response to aridity. A firm understanding of CAM is thus crucial for the development of agricultural responses to climate change. Computational models on CAM have contributed greatly to this understanding. Two types of models have been used so far. Early CAM models based on ordinary differential equations (ODEs) reproduced the typical diel CAM features with a minimal set of components and investigated endogenous day/night rhythmicity. This research brought to light the preponderant role of vacuolar malate accumulation in diel rhythms. A second wave of CAM models used flux balance analysis (FBA) to better understand the role of CO2 uptake in flux distribution. They showed that flux distributions resembling CAM metabolism emerge upon constraining CO2 uptake by the system. We discuss the evolutionary implications of this and also how CAM components from unrelated pathways could have integrated along evolution.